Paraaortic lymph node metastasis in endometrial cancer patients: a comprehensive analysis of rates, survival outcomes, and risk factors through systematic review and meta-analysis - Han, Ling; Chen, Yali; Zheng, Ai; Tan, Xin (Frontiers in Oncology, 2024)
IntroductionThis study aims to explore the incidence of different metastatic patterns in paraaortic lymph nodes and their corresponding survival outcomes in patients with endometrial cancer, as well as to identify the associated risk factors of such metastasis.Material and methodsPubMed, Embase, Cochrane Central Register of Controlled Trials, International Clinical Trials Registry Platform, and Clinical Trials.gov were searched from inception to February 10, 2024.The analysis was conducted using R version 4.2.3.ResultsA total of 47 studies involving 33,425 endometrial cancer patients were analyzed. Meta-analysis results revealed that the rate of isolated paraaortic lymph node metastasis, where pelvic lymph nodes were negative but paraaortic lymph nodes were positive (PLN-PAN+), was found to be 2.58% (95% CI 0.0195-0.0329). The rates for PLN+PAN- and PLN+PAN+ were notably higher at 8.54% (95% CI 0.0642-0.1092) and 8.37% (95% CI 0.0613-0.1090), respectively. For clinical stage I EC, the occurrence rate was 5.92% for PLN+PAN- (95% CI 0.0258-0.1032), 1.00% for PLN-PAN+ (95% CI 0.0081-0.0120), and 2.99% for PLN+PAN+ (95% CI 0.0188-0.0431). The survival outcomes indicate a decreasing trend from the PLN-PAN+ and PLN+PAN- groups to the PLN+PAN+ group. Additionally, the survival outcomes of patients with isolated paraaortic lymph node metastasis appear to be comparable to, or not inferior to, those of the PLN+PAN- group. The analysis indicated that pelvic lymph node metastasis (OR 16.72, 95% CI 10.03-27.86), myometrial invasion ≥50% (OR 5.18, 95% CI 3.09-8.69), lymph-vascular space invasion (LVSI) (OR 3.46, 95% CI 2.49-4.81), cervical invasion (OR 4.00, 95% CI 2.09-7.66), and non-endometrioid cancer (OR 2.39, 95% CI 1.17-4.86) were risk factors for paraaortic lymph node metastasis.ConclusionsIsolated paraaortic lymph node metastasis, though relatively rare, can still occur even in clinical stage I endometrial cancer. The survival outcomes of patients with isolated paraaortic lymph node metastasis appear to be comparable to, or not inferior to, those of the PLN+PAN- group. Even in patients with negative pelvic lymph nodes, careful consideration should be given to the possibility of paraaortic lymph node metastasis, especially in those with high-risk factors.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024503959.